"Now that you mention it": A Survey Experiment on Information, Salience and Online Privacy - Helia Marreiros; Mirco Tonin; Michael Vlassopoulos; m.c. Schraefel (Center for Economic Studies and ifo Institute (CESifo), 2016)
Personal data lie at the forefront of different business models and constitute the main source of revenue of several online companies. In many cases, consumers have incomplete information about the digital transactions of their data. This paper investigates whether highlighting positive or negative aspects of online privacy, thereby mitigating the informational problem, can affect consumers' privacy actions and attitudes. Results of two online survey experiments indicate that participants adopt a more conservative stance on disclosing identifiable information, such as name and email, even when they are informed about positive attitudes of companies towards their privacy. On the other hand, they do not change their attitudes and social actions towards privacy. These findings suggest that privacy concerns are dormant and may manifest when consumers are asked to think about privacy; and that privacy behavior is not necessarily sensitive to exposure to objective threats or benefits of disclosing personal information.
Keywords: C83; L38; M38; 330; survey experiment; information economics; privacy policies; salience; self-disclosure